Association of serum CXCL12 levels with arthropathy in patients with systemic sclerosis. (30th November 2020) - Ikawa, Tetsuya; Miyagawa, Takuya; Fukui, Yuki; Toyama, Satoshi; Omatsu, Jun; Awaji, Kentaro; Norimatsu, Yuta; Watanabe, Yusuke; Yoshizaki, Ayumi; Sato, Shinichi; Asano, Yoshihide
Abstract: Aim: Systemic sclerosis (SSc) is an autoimmune connective tissue disease, in which extensive fibrotic change and vasculopathy affect the skin and various internal organs. It also involves the joints, causing stiffness, arthralgia, and arthritis. Although arthropathy is commonly observed in SSc, its underlying mechanism remains unknown. CXCL12, also known as stromal cell derived factor 1, is associated with inflammation, mesenchymal cell recruitment, angiogenesis, and collagen production, and is implicated in the development of various joint diseases. To assess the potential contribution of CXCL12 to SSc development, we investigated the clinical association of serum CXCL12 levels in patients with SSc. Method: We conducted a cross‐sectional analysis of 68 patients with SSc and 20 healthy controls recruited in a single center over 9 years. Serum CXCL12 levels were measured by enzyme‐linked immunosorbent assay. Results: Serum CXCL12 levels were significantly higher in patients with SSc than in healthy controls (median 1554.0 pg/mL, 25th‐75th centiles 1313.0‐1914.0 pg/mL vs 967.4 pg/mL, 608.8‐1271.0 pg/mL, P  < 0.001). Patients with SSc with elevated CXCL12 levels had significantly more cases of arthropathy than those with normal CXCL12 levels (85.7% vs 25.0%, P  = 0.01). Furthermore, patients with SSc with elevated CXCL12 levels showed an increased trend in the prevalence of limited range of motion of the finger joints compared with those with normal CXCL12 levels (60.0% vs 18.6%, P  =0 .07). Moreover, serum CXCL12 levels were significantly correlated with the titers of rheumatoid factor in patients with SSc ( r  = .41, P  = 0.001). Conclusion: Elevated serum CXCL12 levels may be related to the development of SSc arthropathy.